Meta-Analisis Efektivitas Duolingo Terhadap Penguasaan Kosakata Bahasa Arab - Irfan (CV. SINAR HOWUHOWU, 2024)
This study aims to evaluate the effectiveness of using the Duolingo application in improving Arabic vocabulary mastery through meta-analysis. A total of 6 experimental and quasi-experimental studies published in the last five years were analyzed to assess the impact of Duolingo on vocabulary mastery. The results of the meta-analysis showed a combined effect size value of 0.68, indicating a moderate effect of using Duolingo in learning Arabic vocabulary. However, there was significant heterogeneity between studies, indicating that the effectiveness of Duolingo is influenced by factors such as duration of use, type of features used, and intensity of practice. This study concludes that Duolingo is effective as an Arabic vocabulary learning tool, but is more optimal when used as a complement with other learning methods. Further research is needed to explore how Duolingo can be optimized for other aspects of language skills such as speaking and listening.